Analysis of the Effectiveness and Efficiency of Regional Financial Management of Sigi Regency for the Period 2020-2024 - Fitra, Fitra; Herman Jaya, Andi; Sading, Yunus; Paembonan, Laendatu; Musdayati, Musdayati (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Regional financial management plays a pivotal role in attaining development objectives and enhancing community welfare particularly in fledgling regions like Sigi Regency. Regional governments' fiscal performance gets thoroughly evaluated via wonky effectiveness and efficiency metrics quite essential for assessing resource management skills and revenue goals. The goal of this research is to evaluate the financial performance of Sigi Regency. The study utilised secondary data from the Sigi Regency APBD for the 2020-2024 budget cycle. In order to assess the financial effectiveness and efficiency of the region, the analysis method involved calculating the Effectiveness Ratio and Financial Efficiency Ratio. The findings indicate that, on the whole, the financial effectiveness ratio of Sigi Regency during the 2020-2024 period has reached a highly effective level. This suggests that the local government of Sigi Regency has effectively managed to achieve the expected Regional Original Revenue (PAD), thereby maximising the potential of PAD to support the region's development. Meanwhile, the financial efficiency of Sigi Regency from 2020 to 2024 generally remained at a lower and less efficient level. This indicates that the ratio of revenue to expenditure was not optimal. Even during the periods of 2020, 2021, 2022, and 2024, the efficiency ratio exceeded 100 percent.